Making sense of eastern Asian Late Quaternary hominin variability - Christopher J. Bae; Xiujie Wu (Nature Communications)
A greater degree of Late Quaternary hominin morphological variability is present in eastern Asia than previously assumed. Indeed, a number of distinct populations are present, some that now have new specific names: Homo floresiensis; H. luzonensis; H. longi; H. juluensis. With this piece, we describe the various groupings based on the current hominin fossil record of eastern Asia.